2006
DOI: 10.1111/j.0021-9029.2006.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Directed Thinking on Intentions to Engage in Beneficial Activities: Idea Generation or Mental Simulation?

Abstract: How might people best persuade themselves to engage in beneficial activities, such as dieting, exercise, and studying? One strategy is to think about actions. Another strategy is to think about reasons. In previous research, students who were directed to think about actions increased their study intentions more than did students who were directed to think about reasons. The present experiment tested whether thinking about actions was effective because of idea generation (coming up with the thoughts) or because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Results supported the hypothesis that manipulations designed to enhance the vividness of the imagined scenario (in this case repetition) heightened future intentions. Later research has supported the idea that enhancing the vividness of imagined scenarios will enhance subsequent intentions and behavior, whether this be through thinking specifically about actions (vs. reasons;Ten Eyck et al, 2006); or about process (vs. outcome; Greitmeyer & Wurz, 2005;. In sum, anything that enhances the vividness of the imagined scenario leads to consequently stronger effects on intentions and behavior.…”
Section: Methodsmentioning
confidence: 94%
“…Results supported the hypothesis that manipulations designed to enhance the vividness of the imagined scenario (in this case repetition) heightened future intentions. Later research has supported the idea that enhancing the vividness of imagined scenarios will enhance subsequent intentions and behavior, whether this be through thinking specifically about actions (vs. reasons;Ten Eyck et al, 2006); or about process (vs. outcome; Greitmeyer & Wurz, 2005;. In sum, anything that enhances the vividness of the imagined scenario leads to consequently stronger effects on intentions and behavior.…”
Section: Methodsmentioning
confidence: 94%
“…Imagining actions elicited more positive behavioural intentions towards studying than did thinking about reasons. In a study using similar methodology, Ten Eyck, Labansat, Gresky, Dansereau, and Lord (2006) found that simulation enhanced intentions to a greater extent than did thinking about reasons for a range of beneficial activities (e.g., dieting, studying, and exercising).…”
Section: Imagery Intention and Behaviourmentioning
confidence: 99%
“…The authors also found a positive correlation between the amount of positive projections a person could generate and the size of his social network. Moreover, there is considerable evidence that generating mental images of future success and of the process to get there can sometimes increase achievement motivation, effort, and performance (Greitemeyer & Wu¨rz, 2006;Pham & Taylor, 1999;Taylor et al, 1998;Ten Eyck, Labansat, Lord, & Dansereau, 2006). A positive image of themselves in the future can motivate action by helping people to articulate their goals clearly and develop behaviors that will allow them to fulfill these goals (Pham & Taylor, 1999;Vasquez & Buehler, 2007).…”
Section: Introductionmentioning
confidence: 99%